A Comparative Study between the Outcome of Laparoscopic Appendectomy and Open Appendectomy in Children (Journal of Paediatric Surgeons of Bangladesh, 2015)
Background: Laparoscopic surgery for acute appendicitis in children has been proposed to have advantages over conventional surgery.Introduction: Appendicitis is the most common surgical emergency in childhood. 1 For decades, Open appendectomy (OA) has been the standard treatment for all forms of appendicitis with excellent results.2 Since its description in the early 1980s, laparoscopic appendectomy (LA) became an acceptable approach for simple appendicitis in children.3, 4, 5However, its role in the treatment of complicated appendicitis is controversial. Today, in developed countries about 8% of the population is appendectomized for acute appendicitis during their lifetime.7Materials and method: We are conducting a prospective comparative study with the intention to observe the outcome of 60 purposively selected patients of acute appendicitis in the Department of Pediatric Surgery, Dhaka Medical College & Hospital (DMCH), Dhaka, over a period of 12 months from October, 2013 to October, 2014. The patients are going to be divided into 2 groups by random sampling- Group A- OA Group (patients underwent open appendectomy) and Group B- LA Group (patients underwent laparoscopic appendectomy) for uncomplicated appendicitis. Children up to 14 years are planned to be selected as study subjects. All children are subjected to investigate for white blood cell (WBC) count, plain X- ray KUB region, urine R/E, preoperatively and to observe the amount of analgesics in postoperative pain management and cosmesis on first week, first month, and third month of operation. Structured questionnaire is used to collect information regarding pain, fever, other association preoperatively and operative procedure, duration of operation, per operative findings and post operative follow up. Informed written consent from parents or legal guardian is taken after describing the study objectives. Ethical clearance has been sought from the Ethical Committee of Dhaka Medical College.Results: Total 23 patients are studied till now, 16 in LA group and 7 in OA group. From this limited data we have seen that there is apparently minimum difference between two groups of study population regarding postoperative outcomes.Conclusion: This is an on-going study. Definite conclusion could not be drawn at this preliminary stage. Laparoscopic appendectomy for uncomplicated appendicitis in children is feasible and safe. It is associated with a significantly less use of post operative pain killer, lower incidence of wound infection, and reduced length of hospital stay when compared with patients who had open appendectomy.J. Paediatr. Surg. Bangladesh 5(1): 25-29, 2014 (January)